Comparing the Oncological Outcomes of Cryoablation vs. Radical Prostatectomy in Low-Intermediate Risk Localized Prostate Cancer - Guo, Xiao-xiao; Liu, Sheng-jie; Wang, Miao; Hou, Hui-min; Wang, Xuan; Zhang, Zhi-peng; Liu, Ming; Wang, Jian-ye (Frontiers in Oncology, 2020)
Purpose: To compare the oncologic outcomes of cryoablation (CA) and radical prostatectomy (RP) in patients with low- and intermediate-risk localised prostate cancer (PCa) Materials and Methods: PCa Patients who received CA or RP between 2004 and 2015 were identified from the Surveillance, Epidemiology, and End Results database. Multivariable Cox proportional hazard analysis was used to compare the prostate cancer-specific survival (CSS) and overall survival (OS). We conducted 1:3 propensity score matching and adjusted standardised mortality ratio weighting (SMRW) to balance the clinicopathological characteristics. Results: 97,783 patients were identified after preliminary screening. After matching, the CA and RP groups included 1,942 and 5,826 patients and had median follow-up periods of 85 and 72 months, respectively. CA had lower CSS and OS rates (hazard ratio [HR], 2.07; P = 0.007; HR, 2.09; P < 0.001, respectively) than did RP, which was consistent in the SMRW model (CSM: HR, 2.66; P < 0.001; OS: HR, 2.29; P < 0.001). The 10-year CSS and OS for CA versus RP were 98.1% vs 99.2% and 61.3% vs 79.9%, respectively. Conclusions: In patients with low- to intermediate-risk localised PCa, CA had lower CSS rates than did RP. However, the high 10-year CSS rates indicated that CA could be an option for those who are not RP candidates. Further high-quality trials are needed to confirm and expand our findings.